LECTOTYPIFICATION OF THE CRITICALLY ENDANGERED SUBSHRUB PHYLLANTHUS TALBOTII (PHYLLANTHACEAE) - Singh, R. Kr.; Garg, A. (Edinburgh Journal of Botany, 2016)
The critically endangered Phyllanthus talbotii Sedgw. (Phyllanthaceae) is endemic to the northern part of the Western Ghats in Goa and Karnataka, India. The species was described in 1921 from collections made in 1883, 1918 and 1919, and then rediscovered in 1969. We report here a new locality, Netravali Wildlife Sanctuary, South Goa district, Goa. The species is lectotypified and a detailed description is provided, including distribution, IUCN threat status, conservation measures and nomenclatural notes.